Pesantren dan Mobilitas Sosisal dalam Perspektif Teoretik - Syamsul Arifin (Badan Litbang dan Diklat Kementerian Agama RI, 2010)
In the last decade, we find it difficult to obtain any publication of social mobility of pesantren alumni sociologically referred to as santri community. whereas, any research of the theme can build their image where some people consider pesantren as isolated, while in fact many pesantren alumni play significant roles in the strategic institutions. this study is intended to find a theoretical perspective that can be used for making study of pesantren alumni.